Analisis Kualitas Limbah Cair Pada Kolam Anaerob IV di Instalasi Pengolahan Air Limbah (IPAL) PT. Perkebunan Nusantara VII (Persero) Unit Usaha Bekri - K, Mahfut (Jurusan Biologi UIN Alauddin Makassar, 2013)
Among the industries in Lampung, PT. Perkebunan Nusantara VII (Persero) Bekri Business Unit is one of the Palm Oil Processing Plant (POPP) industry who spend a lot of waste water in the form of residual organic liquid materials. The rest of the liquid material can cause problems such as pollution so it needed special treatment before the waste water is discharged into the environment. This study was conducted to determine the quality of liquid waste in an anaerobic pool IV on Wastewater Treatment Plant (WWTP) PT. Plantation Nusantara VII (Persero) Business Unit Bekri so it can be determined whether the waste water treatment process can improve the quality of waste water for the better. Waste water quality measurement is done using the parameters of physics,chemistry, and heavy metals, namely pH, COD, BOD5, TSS, Cd, Cu, Pb, and Zn. The results showed that the quality of the wastewater in an anaerobic pool IV was good and meets the quality standards of palm oil mill effluent by the State Minister of Environment Resolution No. 03 / MENKLH /11/1991 and the Indonesian Government Regulation No. 20 of 1990 on Water Pollution Control. It also indicates that the effluent treatment system at the Wastewater Treatment Plant (WWTP) PT. Perkebunan Nusantara VII (Persero) Bekri Business Unit is very effective.Keywords: anaerobic pool, liquid waste, PTPN VII